INNOVATION CERAMIC BIOTECHNOLOGY: KEY DIRECTIONS, WAYS OF UTILIZATION AND ADVANTAGES - Raisa A. Platova; Alla V. Ryzhakova; Yuriy T. Platov (Вестник Российского экономического университета имени Г. В. Плеханова)
The article gives a review of works dealing with biological impact on ceramic masses. The authors identify key directions and differences in technology of bio-treatment depending on the type of microorganisms, ways of obtaining and composition of cultural liquid, conditions and method of bio-treatment and natural coenosis of ceramic masses. The impact of cultural liquids with bacteria on rheological properties of ceramic masses was investigated. Surface activity of cultural liquid causes reduction in fluidity and thixotropic strengthening of ceramic dross. Increasing mass of casting is stipulated by rendering hydrophobic to surface of clayish particles of ceramic dross. The experience of using bio-treatment in ceramic industry was discussed.